ImageJ for fluorescence image analysis / Zolkaple Eshak - Eshak, Zolkaple (Faculty of Pharmacy, 2024)
On October 2, 2024, the Imaging Center at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, conducted a four-hour workshop titled "ImageJ for Fluorescence Image Analysis". This online training session was attended by 20 participants from UiTM, Universiti Malaysia Sarawak, the Malaysian Palm Oil Board, Universiti Putra Malaysia, and Universiti Sains Islam Malaysia.